Motivation forces and its influence on female graduates entrepreneurial intentions - Dipa, Tangith Tara; Brac Business School, Brac University (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2023.